Feasibility of a photoelectric sensor technique for nondestructive prediction of granulation disorder in tangerines - Teerachaichayut, S.; Kijpadung, T.; Cheevathumrat, V. (My University, 2019)
Granulation is a physiological disorder in Tangerine (Citrus reticulata) that can cause an internal disorder which cannot be determined by visual inspection. A nondestructive technique, which is simple and low cost, that could determine whether an individual fruit suffered from granulation would be of help to the citrus industry. The intensity signal of photoelectric sensor, when light passed through tangerines 'Keaw Dumnuan' was investigated and showed that the signal was significantly larger (p < 0.05) for normal tangerines and those suffering from granulation. In order to determine a suitable non-destructive method for detect granulation disorder in tangerines that could be applied commercially, a simple and low cost prototype of this photoelectric sensor technique was developed. A set of 52 fruit were used and their average intensity signal from four measurements was used for discriminant analysis. The cut off value of 61.7 mV was used for classification. If a fruit had the signal intensity equal to or less than 61.7 mV, it had granulation, while fruit that had the signal intensity of more than 61.7 mV was normal. Using this signal intensity discrimination the accuracy of classification was 90.4%. It was also shown that the accuracy of prediction was related to the severity of granulation in each fruit. Therefore, the photoelectric sensor technique was shown to be feasible for use in nondestructively detect of granulation in tangerines and be possibly used in future grading systems.